Effectiveness and safety of a less-invasive MCL reconstruction technique for contracted or ossified ligaments in patients with elbow stiffness: An open-label, non-randomised, prospective, multicentre trial in China. (October 2022) - Liu, Wenjun; Xiong, Hao; Wang, Wei; Chen, Shuai; Li, Fengfeng; Liu, Junjian; Yan, Hede; Zhang, Jingwei; Qian, Yun; Fan, Cunyi
Summary: Background: The elbow joint is sensitive to trauma from accidents, sports injuries, and surgical trauma. Some patients develop ossification or contracture of the medial collateral ligament (MCL) after elbow trauma. A less invasive reconstruction of the MCL can be performed after resection of diseased MCL. The biomechanical characteristics of this technique have been demonstrated and validated. However, its clinical effectiveness and safety require further confirmation in clinical practice. Methods: This open-label, non-randomised, prospective, multicentre trial included consecutive patients with elbow stiffness from five orthopaedic centres in China. Patients willing to participate in the study, with elbow stiffness caused by traumatic injury, who had reached skeletal maturity, and who had a range of motion of <100° were eligible for inclusion. Patients with immunological or metabolic causes of elbow stiffness, burns, or central nervous system injuries were excluded. In addition, patients who did not require MCL release and reconstruction after intraoperative release of other structures were also excluded. All patients underwent resection of the diseased MCL part in an open arthrolysis. Medial stability of the elbow was reconstructed using a less invasive MCL reconstruction technique that uses fascia and tendon patches. In this study, the primary outcomes, including stability, Mayo Elbow Performance Score (MEPS), Amadio score, were used to comprehensively evaluate this technique. Outcomes were assessed at 6 weeks, 6 months, and 1 year postoperatively and annually thereafter. This study reports the results of one arm of the trial that has been registered with the Chinese Clinical Trial Registry (chictr.org.cn), ChiCTR-INC-16010019. Findings: Between January 1, 2017 and March 1, 2020, 104 eligible patients were enrolled. The mean follow-up time was 43·47 (95% CI, 41·45 - 45·49) months. Among all 104 patients, 100 (96%) patients who underwent MCL reconstruction retained medial stability at the last follow-up. All outcomes from the last follow-up were used for comparison with the preoperative outcomes. No differences in preoperative and postoperative stability scores were observed ( P = 0·7820). Extension, flexion, pronation, and supination of the injured elbow improved significantly ( P < 0·0001, P < 0·0001, P < 0·0001, P < 0·0001). The mean range of motion (ROM) and forearm rotational range of motion (FRR) increased by 71·25° (152%) ( P < 0·0001) and 30·83° (25%) ( P < 0·0001), respectively. Additionally, the Mayo Elbow Performance Score (MEPS) and muscle strength had increased after evaluation at follow-ups ( P < 0·0001, P < 0·0001). Drastic pain relief and nerve symptom reduction were observed, as evaluated using VAS scores and Amadio scores, respectively ( P < 0·0001, P < 0·0001). Seventeen (16%) patients experienced a recurrence of elbow stiffness of varying severity, but only two patients had poor or fair results. Several common and non-severe complications, including infection in one (1%) patient, new nerve symptoms in seven (7%) patients, new pain in one (1%) patient, fracture in one (1%) patient, and valgus instability in four (4%) patients, were observed and properly treated in this study. Interpretation: The less invasive MCL reconstruction technique using fascia and tendon patches is an effective method for restoring medial stability in patients with elbow stiffness after complete arthrolysis with certain safety. The technique shows prospects for elbow MCL reconstruction in clinical practice. Funding: The study was supported by the National Key Research and Development Program of China (No. 2021YFC2400805), National Natural Science Foundation of China (No. 81830076), Young Elite Scientist Sponsorship Program by Cast (No. YESS20200153), Shanghai Sailing Program (No. 20YF1436000), Shanghai Municipal Science and Technology Commission Foundation (No.19ZR1439200), Municipal Hospital Newly-developing Cutting-edge Technologies Joint Research Program of Shanghai Shenkang Hospital Development Centre (No. SHDC12018130).